Strategic pricing across the product’s sales cycle: a conceptualization - David R. Rink (Innovative Marketing)
Establishing the initial price for a new product is one of the most important decisions a firm will make. Implementing and adjusting this price over the sales cycle of the new product are crucial decisions for both its short- and long-term success. A modification of the product life cycle (PLC) concept is presented to reflect one of the many alternative price-setting strategies available to the company. After justifying and illustrating the modified PLC pricing strategy, applications and limitations are presented and discussed.